Enhancing DevOps with Azure Cloud Continuous Integration and Deployment Solutions - Kothapalli, Kanaka Rakesh Varma (Engineering International, 2019)
This study addresses the critical gap in optimizing DevOps practices within Azure Cloud environments, focusing on continuous integration and deployment solutions. The primary objective is to explore advanced security practices, scalability through architectural patterns, and the integration of compliance and performance monitoring. Key findings indicate that leveraging Azure Security Center and Azure Sentinel significantly enhances data protection and regulatory compliance. Employing scalable architectures, such as microservices and serverless computing, optimizes resource usage and application performance. The integration of Azure Monitor, Log Analytics, and Application Insights ensures comprehensive monitoring, proactive issue detection, and adherence to compliance standards. These strategies collectively improve DevOps efficiency, resulting in faster and more reliable software delivery. Policy implications suggest that organizations should adopt Azure's advanced tools and practices to enhance security, scalability, and compliance in their DevOps processes, ultimately driving operational excellence and continuous improvement in cloud-based applications.
Keywords: DevOps; Azure Cloud; Continuous Integration; Continuous Deployment; CI/CD Solutions; Cloud Automation